Does Vaginal Wall Surgical Trauma During Hybrid Transvaginal NOTES Nephrectomy Have Traumatic Effects On Sexual Functions? A Prospective Study - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (TAYLOR & FRANCIS INC, 2021)
Background: Surgical trauma due to vaginal wall incision to extract the specimen during transvaginal hybrid Natural-Orifices-Transluminal-Endoscopic-Surgery (NOTES) nephrectomy can result in sexual dysfunction and have traumatic psychological impacts. We evaluated the alteration of sexual functions in the postoperative period. Methods: Patients who underwent a transvaginal NOTES nephrectomy were prospectively enrolled. Patients and their partners were evaluated with the Golombok-Rust Inventory of Sexual Satisfaction (GRISS) questionnaire pre- and post-operatively. Surgical characteristics were recorded. Results: Fifty-three patients (mean age: 52.72 +/- 2.39 years; mean tumor size 4.77 +/- 2.55 cm) were included. The total GRISS scores of all patients were similar in pre- and post-operative periods. Although females reported no change in the GRISS score, 60.4% of partners showed a drop in the total score. Non-communication and avoidance subdomains showed significant changes for females; males showed a significant change in avoidance, non-sensuality and dissatisfaction subdomains. Subgroup analyses showed that neither tumor stage nor nulliparous status did not affect total score changes for both genders. The trocar number and perioperative complication rates had no significant effects on total score changes. Conclusion: Sexual function can be affected after transvaginal NOTES nephrectomy and care should include a stringent approach to addressing sexual dysfunction. We support the transvaginal NOTES nephrectomy technique if adequate secondary measures to protect sexual function are taken.
Keywords: Natural orifice transluminal endoscopic surgery; sexual dysfunction; renal cell carcinoma; surgery; sexuality; BREAST-CANCER; SURGERY; WOMEN; FEASIBILITY; IMPACT; SATISFACTION; MULTICENTER; DELIVERY; SAFETY